2007
DOI: 10.1007/s12105-007-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplasia in Different Degrees of Invasion of Carcinoma Ex-Pleomorphic Adenoma

Abstract: Stroma desmoplasia was studied by immunohistochemistry for alpha-smooth muscle actin (alpha-SMA) in 17 instances of carcinoma ex-pleomorphic adenoma (CXPA) classified according to the presence of epithelial and myoepithelial cells and the degree of invasion: intracapsular, minimally and frankly invasive carcinoma. In "resident" pleomorphic adenoma, no desmoplasia was detected. In invasive areas of the intracapsular type of CXPA with only an epithelial component, desmoplasia started to be revealed by the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…They promote tumour progression through "neo-angiogenesis" by releasing growth factors, such as fibroblast growth factor-2 [3] . A study demonstrated that the most migratory and invasive behaviour of tumour cells correlated with the presence of MFs at the invasive tumour front in OSCC because this precedes the invasive stage of the cancer [39,40] . In addition, abundant MFs in the tumour stroma correlates with a higher tumour incidence, specifically in patients aged below 60 years [19] .…”
Section: Mfs In Osccmentioning
confidence: 99%
See 2 more Smart Citations
“…They promote tumour progression through "neo-angiogenesis" by releasing growth factors, such as fibroblast growth factor-2 [3] . A study demonstrated that the most migratory and invasive behaviour of tumour cells correlated with the presence of MFs at the invasive tumour front in OSCC because this precedes the invasive stage of the cancer [39,40] . In addition, abundant MFs in the tumour stroma correlates with a higher tumour incidence, specifically in patients aged below 60 years [19] .…”
Section: Mfs In Osccmentioning
confidence: 99%
“…In wound healing, MFs transiently acquire the phenotype [1] , which persists during fibrosis in the tumour environment because of an imbalance between the apoptosis and the proliferation of transformed cells leading to disease progression [40] .…”
Section: Functional Similarities and Differences Between Wound Healinmentioning
confidence: 99%
See 1 more Smart Citation
“…RTE has shown promising results for differentiating between malignant and benign lesions in breast lumps [11], prostate tumors [12,13], thyroid nodules [14 -16], lymph nodes [17,18] and the pancreas [8,19]. Both malignant tumors and chronic inflammation may lead to the formation of soft tissue fibrosis [20,21]. Fibrosis formation in malignant tumors is called desmoplasia and may contribute to increased tissue hardness through several mechanisms involving tumor cells, stromal cells and the extracellular matrix [22].…”
mentioning
confidence: 99%
“…Strain imaging depends on several factors contributing to increased tissue hardness: increased fibrosis and desmoplastic reaction. The latter is typical of malignant tumors of the breast, bowel, and pancreas [25,26]. Increased interstitial fluid pressure (IFP) may also increase tissue incompressibility.…”
Section: Discussionmentioning
confidence: 99%